Juggling Two Balls—Smoking (Re)Normalization and Harm Reduction: E-Cigarettes—Facts and Misconceptions in Taiwan. (May 2018) - Gao, Wayne; Sanna, Mattia; Huang, Li-Ling; Chiu, Ya-Wen; Chen, Yi-Hua; Chiou, Hung-Yi
The increasing popularity of e-cigarettes, especially among adolescents, has alarmed health advocates and government officials, dominating the tobacco control narrative in the past few years. According to the Global Youth Tobacco Survey, the percentage of Taiwanese teenagers reporting use of e-cigarettes in the past 30 days rose from 2.01% (95% confidence interval [CI] = 1.82% to 2.23%) in 2014 to 3.54% (95% CI = 3.30% to 3.80%) in 2017. However, during the same period, prevalence of cigarettes declined from 11.51% (95% CI = 9.84% to 13.42%) to 8.26% (95% CI = 7.80% to 8.76%) among senior high school students, and from 5.00% (95% CI = 4.36% to 5.74%) to 2.66% (95% CI = 2.38% to 2.96%) among junior high school students, with figures for both groups reaching historical lows. This trend is similar to population-level trends observed in both the United Kingdom and the United States, but only future long-term studies will be able to clarify if it is consistent or not with the fears that e-cigarette may act as a "gateway" to cigarette smoking renormalization.